Bridging the Gap between Language and Literature: Teaching English in Bangladesh at Tertiary Level - Nusrat, Masrufa (ELT WORLDWIDE, 2015)
Using literary material for developing language skills has once again achieved much rationale for both L1 and L2 learners in the last two decades. In my paper I would like to explore the possibilities and loopholes of teaching language through literature in Bangladesh at tertiary level by providing a birdâs eye-view of survey into the reality of our language classrooms. Our English language classes follow traditional lecture-based teaching techniques and use almost no literary materials for teaching language. Mostly âreferentialâ materials are taught by Communicative Language Teaching (CLT) method which are exclusively confined to everyday real-life situational use and does not engage learnersâ imaginative faculties. Therefore, in this paper I have tried to demonstrate how literary texts or ârepresentational textsâ can develop English proficiency, foster critical thinking and involve learners in creative language use. I have also critiqued our teaching approaches; student evaluation; irrelevant material selection and rote learning during exam. As a result the gap between language and literature in our academia is widening and hampering adequate language acquisition. Although critical practices like- Literary Theory and Cultural Studies have come to academic forefront and impressive curriculum such as- World Literature in English, Comparative Literature and Applied Linguistics and ELT gained much popularity, learnersâ basic linguistic competence failed considerably. I have tried to recommend ways to solve these problems by bridging the gap between language and literature by introducing language-based teaching approach and integrating language and literature in our English classrooms. Keywords: representational material, referential material, language-based approach, stylistics, literature with a small âlâ, literary language, imaginative language use, literary and linguistic competence